Apical root resorption of maxillary first molars after intrusion with zygomatic skeletal anchorage - (:unkn) unknown (My University, 2005)
The aim of this study was to evaluate radiographically the apical root resorption of maxillary first molars after their intrusion was done using zygomatic miniplates as skeletal anchorage in open-bite cases. The study group comprised 16 consecutively treated open-bite cases who had received special titanium miniplates in their zygomatic bones for use as anchorage to apply orthodontic intrusive forces to the maxillary posterior region. The control group consisted of 16 patients, who were matched regarding age, sex, and treatment duration but who had undergone fixed orthodontic treatment without intrusion mechanics for molars. Tooth lengths were measured on pretreatment, and posttreatment panoramic radiographs of all patients and mesiobuccal and distobuccal roots of left and right maxillary first molars were measured on-screen using a software program. The difference between the pre- and posttreatment tooth lengths was defined as apical root resorption. Comparison of the differences in root resorption of the two groups using the t-test for independent samples showed a statistically significant difference (P = .004) only for mesial roots on the right side. But because the mean difference in apical root resorption was only 0.5 mm, it was concluded that the apical root resorption of maxillary first molars after intrusion was done using zygomatic skeletal anchorage was not clinically significant.
Keywords: Adult; Female; Humans; Adolescent; Male; Maxilla; Tooth Movement Techniques; Open Bite; Orthodontic Anchorage Procedures; Radiography; Zygoma; Tooth Apex; Molar; Root Resorption; Bone Plates; Dental Records; Miniaturization